(untitled) (Research, Society and Development, 2021)
COVID-19 is a disease caused by the SARS-CoV-2 virus. The first case of this disease was reported in Wuhan, China. The virus quickly spread causing a worldwide pandemic. The therapeutic approach for this infection requires an expanded look, which considers the physiological and social consequences of the disease, therefore, it is necessary the support of a team composed of several health professionals that act in an articulate and collaborative way. This work aims to identify the scientific literature that deals with the work of the multidisciplinary team in the face of the pandemic. An integrative literature review was carried out from April to August 2020. It was identified twenty-eight articles compatible with the objective of this study, predominantly found in the PubMed database, carried out in Brazil and published in 2020. The several health impacts caused by this disease are evident, thus requiring a multi-professional approach. Multi-professional work favors comprehensive health care and contributes to the effectiveness of health services in this time of pandemic.The scientific literature brings findings that reflect the contribution of the multidisciplinary team in this context.